Eccrine porocarcinoma of the head and neck: Meta‐analysis of 120 cases. Issue 9 (21st April 2020) - Le, Nguyen‐Son; Janik, Stefan; Liu, David T.; Grasl, Stefan; Faisal, Muhammad; Pammer, Johannes; Schickinger‐Fischer, Bettina; Hamzavi, Jafar‐Sasan; Seemann, Rudolf; Erovic, Boban M.
Abstract: Background: The aim of the study is to analyze potential prognostic factors and to evaluate therapy strategies regarding clinical outcome in patients with eccrine porocarcinoma (EPC) of the head and neck. Methods: One hundred and sixteen EPC cases from ninety studies and four authors' EPC cases were included in the meta‐analysis. Results: At an average follow up of 20.48 months, the 3‐year overall survival and regional recurrence rate were 70.3% and 19.0%, respectively. Patients without surgical treatment had a significantly worse 3‐year overall survival. Mohs microscopic surgery led to significantly less occurrence of regional recurrences compared to wide excision. An ulcerating lesion, high mitotic activity, and lymphovascular invasion were significant prognostic factors. Conclusion: Surgical resection is the cornerstone in the therapy of EPC and represents the therapeutic modality that offers the best chance of disease‐free survival. Due to the high probability of recurrence, close follow‐ups are strongly recommended.